Perceived stress may mediate the relationship between antenatal depressive symptoms and preterm birth: A pilot observational cohort study. - Sharifa Lalani; Aliyah Dosani; Ntonghanwah Forcheh; Shahirose Sadrudin Premji; Sana Siddiqui; Kiran Shaikh; Ayesha Mian; Ilona S Yim; Maternal-infant Global Health Team (MiGHT) Collaborators in Research (PLoS ONE)
Background Screening for changes in pregnancy-related anxiety and depressive symptoms during pregnancy may further our understanding of the relationship between these two variables and preterm birth. Objectives To determine whether changes in pregnancy-related anxiety and depressive symptoms during pregnancy influence the risk of preterm birth among Pakistani women; explore whether perceived stress moderates or mediates this relationship, and examine the relationship between the various components of pregnancy-related anxiety and preterm birth. Methods A prospective cohort study design was used to recruit a diverse sample of 300 low-risk pregnant women from four centers of Aga Khan Hospital for Women and Children in Karachi, Pakistan. Changes in pregnancy-related anxiety and depressive symptoms during pregnancy were tested. Multiple logistic regression analysis was used to determine a predictive model for preterm birth. We then determined if the influence of perceived stress could moderate or mediate the effect of depressive symptoms on preterm birth. Results Changes in pregnancy-related anxiety (OR = 1.1, CI 0.97-1.17, p = 0.167) and depressive symptoms (OR = 0.9, CI 0.85-1.03, p = 0.179) were insignificant as predictors of preterm birth after adjusting for the effects of maternal education and family type. When perceived stress was added into the model, we found that changes in depressive symptoms became marginally significant after adjusting for covariates (OR = 0.9, CI 0.82-1.01, p = 0.082). After adjusting for the mediation effect of change in perceived stress, the effect of change in depressive symptoms on preterm birth were marginally significant after adjusting for covariates. Among six different dimensions of pregnancy-related anxiety, mother's concerns about fetal health showed a trend towards being predictive of preterm birth (OR = 1.3, CI 0.97-1.72, p = 0.078). Conclusions There may be a relationship between perceived stress and antenatal depressive symptoms and preterm birth. This is the first study of its kind to be conducted in Pakistan. Further research is required to validate these results.